Fragility analysis of curtain walls based on wind-borne debris considering wind environment. (January 2023) - Lyu, Meng-Ze; Ai, Xiao-Qiu; Sun, Ting-Ting; Chen, Jian-Bing
Abstract: Increasing attention has been attached to the risk assessment and fragility analysis of envelopes of high-rise buildings subjected to the impact of wind-borne debris in hurricanes or typhoons. A probabilistic model of wind-borne debris is proposed in the present paper for risk assessment and fragility analysis of high-building curtain walls based on the numerical solution of three-dimensional flight trajectories of debris and the computational fluid dynamics simulation of local wind environment in a residential area. The influence of sources of randomness in the generation of debris, such as generated location, size, and initial attack angle, as well as local wind environment, on the location of debris impacting on the building curtain wall and the impact damage effect, are considered in the proposed model. The evolution of the probability characteristics of debris is driven by its physical flying behavior in the local wind environment, and the failure probability of each piece of glass of building curtain walls impacted by debris can be determined. Furthermore, a numerical algorithm is given for the fragility analysis under different incoming wind speeds, which can be used to determine the vulnerability and the fragility curve. Finally, two numerical examples for application to residential areas are provided. Results show that the proposed model can provide evaluation and prediction for wind disaster risk and fragility of high-rise buildings in urban areas.